2003
DOI: 10.1165/rcmb.2002-0321oc
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Antioxidant-Related Gene Expression in the Airway Epithelium of Cigarette Smokers

Abstract: Cigarette smoking is the major risk factor for developing chronic bronchitis, yet only 15-20% of smokers develop this disorder. Because oxidants are the major mechanism of smoking-induced airway damage, we hypothesized that smoking is associated with upregulation of various antioxidant-related genes in the airway epithelium, but the magnitude of the response shows high interindividual variability. Microarray analysis was used to assess levels of expression of 44 antioxidant-related genes in four categories (ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
181
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(202 citation statements)
references
References 42 publications
20
181
1
Order By: Relevance
“…64 We found no difference in serum catalase levels. This results agrees with that of Hackett et al, 65 who reported that humans do not up-regulate catalase genes in the airway epithelium in response to oxidative stress.…”
Section: Discussionsupporting
confidence: 93%
“…64 We found no difference in serum catalase levels. This results agrees with that of Hackett et al, 65 who reported that humans do not up-regulate catalase genes in the airway epithelium in response to oxidative stress.…”
Section: Discussionsupporting
confidence: 93%
“…They did wholegenome gene expression profiling of punch biopsies from the buccal mucosa of 40 healthy smokers and 40 healthy nonsmokers, a relatively large study for a global comparison of gene expression. Smoking-related gene expression changes identified in the mouth were very similar to previously published gene expression changes in the bronchial epithelium of active smokers (10). This new study also identified several genes that were more strongly induced or suppressed by smoking in women, an intriguing observation given data that have suggested that women may have an increased lung cancer risk (versus men) in association with a given amount of cumulative tobacco smoke exposure.…”
Section: Introductionsupporting
confidence: 85%
“…Our group and others previously have shown that genome-wide gene expression profiling of bronchial airway epithelial cells collected in bronchoscopic brushings reflects the physiologic response to cigarette smoke exposure and the irreversibility of a number of these responses/ changes after smoking cessation (10)(11)(12)(13). Prior studies have also shown that gene expression profiles in the cytologically normal bronchial airway epithelium can distinguish, with high sensitivity and specificity, smokers with and without lung cancer and can serve as a clinically relevant diagnostic biomarker (14)(15)(16).…”
Section: Introductionmentioning
confidence: 85%
“…61,62 In humans, Gpx-1 has been shown to be increased in COPD, 63 and Gpx-2 showed a three-to five-fold up-regulation in epithelial cells of smokers compared with nonsmokers. [64][65][66] Gpx-3 showed a two-fold up-regulation in epithelial cells of smokers compared with nonsmokers. 65,67 There was little evidence of differential regulation of Gpx-4, Gpx-5, or Gpx-7 by disease status.…”
Section: Gpxs In Normal Physiology and Lung Diseasesmentioning
confidence: 89%